Pilot study on peripheral neuropathy prevalence in adults diagnosed with type 2 Diabetes mellitus in Primary Health care in Divinópolis – Brazil (Research, Society and Development, 2021)
Introduction: Type 2 diabetes mellitus (DM2) greatly impacts public health due to its epidemiological importance. As for its complications, these can be macro and microvascular. At the microvascular level, diabetic peripheral neuropathy (DPN) plays a role of considerable relevance, being this the most common and disabling. Its prevalence is closely related to the population studied, which ranges from 13 to 47%. Objective: To carry out a pilot project that serves as a model for measuring the prevalence of DPN in a determined population of diabetic patients, taking as an example the city of Divinopolis - Brazil. Methods: Five primary health care units in Divinópolis were randomly selected and a sample of 75 users diagnosed with DM2 was also randomly obtained. After selection, the Michigan Neuropathy Classification Instrument (MNSI-BRASIL) was applied. This instrument provided scores that may suggest the presence of NPD through a self-administered questionnaire and physical examination of the feet. Results: After applying the Michigan Neuropathy Classification Instrument (MNSI-BRASIL) a prevalence of NPD of 44% was found, and the prevalence in each unit was: Belvedere II 40%, São José 56%, Serra Verde 38, 46 %, Central 66.6% and Niterói 33.3%. Conclusion: The findings demonstrate positive and negative points regarding the study design used and the assessment instrument used. Thus, the present work will serve as a substrate for future studies on NPD prevalence in Adults with DM2.